Base nacional comum curricular (BNCC) para a educação infantil: estudo e implementação em uma creche do município de São Bernardo do Campo - Lima, Meire Cardoso de (2020)
The object of this intervention research is the National Common Curricular Base (BNCC) for Early Childhood Education and its implementation in a daycare center, guided by the following questions: How to implement the BNCC in a daycare center critically considering from the political pedagogical process (PPP) to the to current practices? What is the role of educators in this proposal by fields of experience? What challenges and possibilities are evident in this process of discussion and transformation? The general objective was to analyze how the process of implementing the BNCC for Early Childhood Education occurs in a daycare center in São Bernardo do Campo. Specific objectives we outline include: Verify the role of educators in this proposal by fields of experience and identify the challenges and possibilities that are evident in this process of discussion and transformation. We start from the hypothesis that for the implementation of the BNCC to be done in a structured way in order to compare the PPP to the pedagogical practices, the proposal must be studied critically with all the educators involved, reflecting on the transformations and possibilities of work required, thus making it possible to overcome the mere bureaucratic attendance required by the current documents, resonating directly in the pedagogical routine shared with the children and their families, overcoming some rigid methods, routines and practices that have already crystallized. The methodology used was of a qualitative nature and intervention type, and the instruments of data collection were observation of the teachers' practices, analysis of the training strategies of the training meetings, and part of the pedagogical documentation produced during the execution of the training plan. We based the theoretical framework on authors of critical pedagogy. Analyzing the formative meetings, we list two categories: continuing education and the learning experience of teachers. The results show that the implementation of BNCC is a complex process in which it will be necessary for the formative meetings to be based on the learning experience of teachers and other educators of the school team. However, the fact that the professionals involved in this study committed themselves at that time to the proposed readings and to the training offered has given new meaning to their pedagogical practices, making the school space more welcoming for children and bringing their teaching more intentionality.